2015
DOI: 10.1002/chem.201501550
|View full text |Cite
|
Sign up to set email alerts
|

Are Copper(I) Carbenes Capable Intermediates for Cyclopropanations? The Case for Ylide Intermediates

Abstract: A novel approach is used to synthesize a stable, ligated copper(I) carbene in the gas phase that is capable of typical metal carbenoid chemistry. However, it is shown that copper(I) carbenes generally undergo rapid unimolecular rearrangements including insertions into copper-ligand bonds and Wolff rearrangements. The results indicate that most copper(I) carbenes are inherently unstable and would not be viable intermediates in condensed-phase applications; an alternative intermediate that is less prone to rearr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 81 publications
(144 reference statements)
0
6
0
Order By: Relevance
“…45 This study also addressed the problem of how to avoid the wellknown tendency of copper(I) carbenes to undergo intramolecular rearrangements, e.g., Wolff rearrangement or insertion into copper−ligand bonds, by forming copper(I) carbene ylides through complexation with solvents or weak nucleophiles. 45 5) have been observed (eq 2), these processes are either not very efficient (n = 1) or do not result in carbon−carbon bond formation upon dehydrogenation of CH 4 (n = 5). 46,47 Similarly, the efficiency of Fischer−Tropsch-type coupling of methylene units (eq 3) has been reported to depend crucially on the nature of the transition metal M. 48,49…”
Section: ■ Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…45 This study also addressed the problem of how to avoid the wellknown tendency of copper(I) carbenes to undergo intramolecular rearrangements, e.g., Wolff rearrangement or insertion into copper−ligand bonds, by forming copper(I) carbene ylides through complexation with solvents or weak nucleophiles. 45 5) have been observed (eq 2), these processes are either not very efficient (n = 1) or do not result in carbon−carbon bond formation upon dehydrogenation of CH 4 (n = 5). 46,47 Similarly, the efficiency of Fischer−Tropsch-type coupling of methylene units (eq 3) has been reported to depend crucially on the nature of the transition metal M. 48,49…”
Section: ■ Introductionmentioning
confidence: 96%
“…On the basis of energetic considerations, a dissociation−association pathway has been ruled out in favor of a methylene-transfer process for the CH 2 → RCHCH 2 ligand exchange at the copper site. 45 This study also addressed the problem of how to avoid the wellknown tendency of copper(I) carbenes to undergo intramolecular rearrangements, e.g., Wolff rearrangement or insertion into copper−ligand bonds, by forming copper(I) carbene ylides through complexation with solvents or weak nucleophiles. 45 5) have been observed (eq 2), these processes are either not very efficient (n = 1) or do not result in carbon−carbon bond formation upon dehydrogenation of CH 4 (n = 5).…”
Section: ■ Introductionmentioning
confidence: 99%
“…We have shown previously that gold­(I) and other metal-stabilized carbenes are prone to rearrangements leading to ylide species (i.e., addition of a nucleophilic atom to the carbene) . We have also shown that these ylides can potentially undergo carbene-like reactions.…”
Section: Resultsmentioning
confidence: 99%
“…33 We have shown previously that gold(I) and other metalstabilized carbenes are prone to rearrangements leading to ylide species (i.e., addition of a nucleophilic atom to the carbene). 19 We have also shown that these ylides can potentially undergo carbene-like reactions. Species I and III are essentially carbenes stabilized by coordination to the acetate carbonyl and are analogues to the ylides we have identified as carbene surrogates (each has an ylide resonance form).…”
Section: ■ Introductionmentioning
confidence: 84%
See 1 more Smart Citation